An analysis of Southern Africa's food safety standards within the broader framework set by the WTO's SPS measures: a South African case study - Mukumba, Chenai (My University, 2011)
This dissertation seeks to identify the existence of the International Food Safety Complex (IFSC) within the international arena. The analysis of the IFSC also contributes to an emerging area of research about international institutional complexes, in particular how they emerge and form functional niches. The IFSC is examined in light of Southern Africa where the notions of the timing and absolute demand for international institutions adds dynamics that have not yet been considered in international institutional literature. This dissertation assesses how food safety regulation in the Southern African region functions in light of a cooperative IFSC and uses South Africa as a case study to offer some insight into the opportunities and challenges that exist in the African region